The role of social media towards fomenting radicalization among youth in Bangladesh - Purnata Talukder; Sakin Tanvir (SIMULACRA: JURNAL SOSIOLOGI, 2022)
The purpose of the study is to identify the role of social media in spreading radicalization among Bangladeshi youth and the factors behind them. The concepts of radicalization and violent extremism have become increasingly prevalent in global politics and development programming during the last few decades and the youths are getting involved through social media from the contents published by the extremist groups. The authors have used qualitative method to understand and scrutinize the findings of the study. In these processes, they have chosen secondary data analysis from articles, journals, books, newspaper etc. in order to collect and analyze data. Finally, they have tried to find out the factors behind the involvement of youths in radicalization and extremist acts through social media, the preventive measures taken by the Government of Bangladesh (GoB) and further possible initiative to boost up the preventive techniques to safeguard the youths. In the consequences, the authors assumed that lack of religious knowledge, adventurous nature, economic factors, cultural factors and identity crisis could be the reasons behind the vulnerability of youths involving in radicalization in Bangladesh.